Determining the Effects of Differential Expression of GRKs and β-arrestins on CLR-RAMP Agonist Bias - Pearce, Abigail; Redfern-Nichols, Theo; Harris, Matthew; Poyner, David R.; Wigglesworth, Mark; Ladds, Graham (Frontiers in Physiology, 2022)
Signalling of the calcitonin-like receptor (CLR) is multifaceted, due to its interaction with receptor activity modifying proteins (RAMPs), and three endogenous peptide agonists. Previous studies have focused on the bias of G protein signalling mediated by the receptor and receptor internalisation of the CLR-RAMP complex has been assumed to follow the same pattern as other Class B1 G Protein-Coupled Receptors (GPCRs). Here we sought to measure desensitisation of the three CLR-RAMP complexes in response to the three peptide agonists, through the measurement of β-arrestin recruitment and internalisation. We then delved further into the mechanism of desensitisation through modulation of β-arrestin activity and the expression of GPCR kinases (GRKs), a key component of homologous GPCR desensitisation. First, we have shown that CLR-RAMP1 is capable of potently recruiting β-arrestin1 and 2, subsequently undergoing rapid endocytosis, and that CLR-RAMP2 and -RAMP3 also utilise these pathways, although to a lesser extent. Following this we have shown that agonist-dependent internalisation of CLR is β-arrestin dependent, but not required for full agonism. Overexpression of GRK2-6 was then found to decrease receptor signalling, due to an agonist-independent reduction in surface expression of the CLR-RAMP complex. These results represent the first systematic analysis of the importance of β-arrestins and GRKs in CLR-RAMP signal transduction and pave the way for further investigation regarding other Class B1 GPCRs.